The structure of the deferred income tax and its influence on indicators describing the economic performance of commercial insurance companies - Hana Bohušová (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2007)
The main objective of this paper is presentation of findings gathered through an analysis of items that cause deferred income tax in commercial insurance companies in the Czech insurance market. The evaluation of the subject is focused in accordance with the concept of the presented paper as regards structure analysis of the deferred tax, working with a selection of insurers – members of the Czech Insurance Association. We study, document and evaluate the influence of the deferred income tax being related with the given available income, as well as related to the effective income tax rate in a commercial insurance company. This analysis concerns the evaluation of the present-day degree of transformation and approximation of the Czech system of insurance in the process of harmonization with the European insurance system.